Increasing Prevalence of HIV Pretreatment Drug Resistance in Women But Not Men in Rural Uganda During 2005–2013 - McCluskey, Suzanne M.; Lee, Guinevere Q.; Kamelian, Kimia; Kembabazi, Annet; Musinguzi, Nicholas; Bwana, Mwebesa B.; Muzoora, Conrad; Haberer, Jessica E.; Hunt, Peter W.; Martin, Jeffrey N.; Boum, Yap; Bangsberg, David R.; et al. (AIDS patient care and STDs, 2018)
The prevalence of HIV pretreatment drug resistance (PDR) is increasing in sub-SaharanAfrica.We sought to describe correlates of PDR and evaluate effects of PDR on clinical outcomes in rural Uganda. We analyzed data from the Uganda AIDS Rural Treatment Outcomes study, a cohort of antiretroviral therapy (ART)-naive adults with HIV (2005–2015). We performed resistance testing on pre-ART specimens. We defined PDR as any World Health Organization (WHO) 2009 surveillance drug resistance mutation and classified PDR level using the Stanford algorithm. We fit unadjusted and sex-stratified log binomial regression and Cox proportional hazardmodels to identify correlates of PDR and the impact of PDR on viral suppression, loss to follow-up (LTFU), and death. We analyzed data from 738 participants (median age 33 years, 69% female). Overall, prevalence of PDR was 3.5% (n = 26), owing mostly to resistance to non-nucleoside reverse transcriptase inhibitors. PDR increased over time in women (1.8% in those enrolling in clinic in 2001–2006, vs. 7.0% in 2007–2013; p = 0.006), but not in men (1.15% vs. 0.72%, p = 0.737). Lower pre-ART log10 HIV RNA was also associated with higher prevalence of PDR. We identified longer time to viral suppression among those with PDR compared with without PDR (0.5 and 0.3 years, respectively, p = 0.023), but there was no significant relationship with mortality or LTFU ( p = 0.139). We observed increasing rates of PDR in women in southwestern Uganda. Implications of this trend, particularly to prevention of mother-to-child transmission programs in the region, require attention due to delayed viral suppression among those with PDR.
Keywords: HIV-1; Resistance; Antiretroviral therapy; Viral suppression; Sub-Saharan Africa